Asymmetric epileptic spasms after corpus callosotomy in children with West syndrome may be a good indicator for unilateral epileptic focus and subsequent resective surgery. Issue 3 (1st August 2022) - Uchida, Daiki; Ono, Tomonori; Honda, Ryoko; Watanabe, Yoshiaki; Toda, Keisuke; Baba, Shiro; Matsuo, Takayuki; Baba, Hiroshi
Abstract: Objective: This retrospective study was designed to observe differences in ictal movements of epileptic spasm (ES) before and after corpus callosotomy (CC). We hypothesized that asymmetric expression of ES is more clarified after CC and would be a good indicator for the epileptic hemisphere. Methods: We selected 16 patients with intractable ES in West syndrome who were seizure‐free after CC and subsequent resection or disconnective surgery of the unilateral hemisphere. We retrospectively reviewed their behavioral ES recorded at video‐electroencephalography monitoring before and after CC. Asymmetric neck flexion (NF) and involuntary muscular contraction of the upper and lower extremities (MCU and MCL, respectively) were primarily described correlating their laterality and the responsible hemisphere proved by surgical resection. Results: Asymmetric NF, MCU, and MCL could be found both before and after CC. However, the percentage of those movements to the total number of ES increased after CC; asymmetric NF, 82.9% vs. 20.1%; unilaterally predominant MCU, 81% vs. 39.3%; and unilaterally predominant MCL, 77.6% vs. 29.9%. Regarding asymmetric NF, the direction in which the neck flexed or the head turned was significantly ipsilateral to the responsible hemisphere in 9 of 12 patients after CC (75%). The predominant side of MCU and MCL were significantly contralateral to the responsible hemisphere in 11 of 11 and 7 of 9 patients (100% and 77.8%, respectively). Significance: Asymmetric NF, MCU, and MCL were clarified in patients with ES who were successfully treated with CC and subsequent surgery. Those changes in ictal behaviors after CC may indicate the lateralization of epileptic activity and encourage more curative surgical treatment.